Optimalisasi Ovitrap Dalam Mendukung Program 3R Untuk Pengelolaan Sampah dan Pengurangan Risiko DBD - Fortuna, Celine; Mandira, I Made Chandra; kholid, Kholid (LPPPM STAI Darul Hikmah Bangkalan, 2025)
Waste management is an important topic in a variety of fields, including Padangsambian Kaja village. 3R Programs (Reduction, Reuse, Recycling) are effective solutions to reduce the negative impact of waste on the environment. One way this program can be supported is Ovitrap, which helps to control mosquito breeding and at the same time reduce organic waste. The purpose of this study is to evaluate the application of the Ovitrap method in supporting SDN 2 Padangsambian 3R programs in Padangsambian Kaja Village. Methods used include in-person observations and interviews with school staff and the community. The results show that the use of organic waste in ovitrap, environmental awareness, and the decline in mosquito populations around schools may be reduced. The program will have a positive effect on more efficient waste management and improve environmental quality in and around SDN 2 Padangsambian.